Epigenetics: molecular mechanisms and implications for disease. - Handel, A; Ebers, G; Ramagopalan, S (2010)
Epigenetics is rising to prominence in biology as a mechanism by which environmental factors have intermediate-term effects on gene expression without changing the underlying genetic sequence. This can occur through the selective methylation of DNA bases and modification of histones. There are wide-ranging implications for the gene-environment debate and epigenetic mechanisms are causing a reevaluation of many traditional concepts such as heritability. The reversible nature of epigenetics also provides plausible treatment or prevention prospects for diseases previously thought hard-coded into the genome. Here, we consider how growing knowledge of epigenetics is altering our understanding of biology and medicine, and its implications for future research.